A instrução na educação de surdos produzida na modernidade: a tríplice condução de surdos-professores - Carvalho, Daniel Junqueira (2023)
The research in this thesis problematizes the matter of deaf education in modern times and its conduct practices. Since the founding of the institute by the Abbé de l'Épée, the fruits of his work, after his death, were taken over by the Abbé Sicard, who followed the same model of production with deaf-mute pupils. Some of the questions that guide our work are: When his deaf-mute pupils became the first repeaters and teachers, what was their role? What did they teach? Was it the same model as l'Épée and Sicard or not? Did they only teach signs for objects and signs for words? Did they have a specific method? How were they similar or different? How did they become repeaters and teachers for the deaf and dumb? Were there any rituals? What were the conducting practices of deaf-mute teachers like? Did the deaf-mute teachers show any resistance, or were they submissive to the practices of instruction by the abbots? These questions make it possible to look at things in different ways, as well as to think and act grounded on a problematization of how modernity has contributed to observing the forms and ways of a threefold conduction. Thus, in a challenging and risky way, I set out my central objective: to understand the practices of a threefold conduction of deaf-mutes in the 18th-19th centuries that produce the governing of themselves and others. As specific objectives, this thesis sought to analyze the discourses that were spread and contextualized in that time and space, building an analogy with our time: 1) to identify the documents of those who wrote about the linguistic instruction of deaf-mutes with the abbots l'Éppé and Sicard (1786); 2) to discuss the threefold conduction (philosopher, teacher, and politician) of the deaf-mutes Pierre Desloge (1779), Jean Massieu (1808-1820), Laurent Clerc (1815, 1818) and Ferdinand Berthier (1873); and 3) to problematize in the documents the practices of linguistic instruction of self and other subjects. Based on theorizations, we use one in the Platonic dimension by the threefold conduction and the other by governing oneself and others in the Foucauldian line of vision. This work intends to problematize this threefold conduction of deaf people and how it emerges in modernity in deaf education. The other question is: What were the governing oneself and others for deaf-mute subjects in the 18th and 19th centuries practices? The data that makes up an archive was used from the following series of documents: 1) Note G of the book l'Abbé Sicard (Ines historical series, volume 4) which deals with the letters exchanged between Abbé l'Épée and Abbé Sicard (1786); 2) Observations d'un sourd et muèt, sur un cours Élémentaire d'Éducation des sourds et muèts (Pierre Desloges, 1779); 3) Biographies de Jean Massieu - La reconnaissance est la mémoire du coeur (1808-1820); 4) Recueil des définitions et réponses les plus remarquables de Massieu et Clerc Sourds-Muets aux diverses questions qui leur ont été faites dans les séances publiques de M. L'abbé Sicard (1815); 5) Discours à l'examen des élèves (Laurent Clerc, 1818); 6) The banquets of the deaf and dumb (work on Ferdinand Berthier, 1834-1848) and 7) Abbé Sicard, a famous teacher of the deaf and dumb, immediate successor to the Abbé de l'Épée - Historical account of his life, his work and his successes (Ferdinand Berthier, 1873 – translated in 2012). In considerations that do not need to end, the results of the data analysis have shown us the practice of the triple conduct of each person, of the deaf-mutes and of the abbots, who at various times are conductors of the conduct of themselves (as philosophers), of others (as teachers) and, finally, of everyone (as politicians). The practices of the threefold conduct continue today in different ways and other modifications of the conduct of self, others, and everyone.